Adapting Sources of Middle School Mathematics Self-Efficacy Scale to Turkish Culture - Hakkı Kontas; Bahadır Ozcan (Institute of Advanced Engineering and Science, 2017)
The purpose of this study was to adapt the Sources of Middle School Mathematics Self-Efficacy Scale developed by Usher and Pajares to Turkish culture. This scale assesses Bandura’s theorized sources of self-efficacy among mathematics students in middle school. After the Turkish version of the scale was formed, it was applied 6th, 7th and 8th grades 282 middle school students (157 girls and 125 boys). Results of Confirmatory Factor Analysis (CFA) showed good fit indeces; χ2/sd= 2.25, RMSEA= .06, CFI= .98, NNFI= .97 and SRMR= .05. These values indicated that the proposed four factor model was acceptable for this Turkish sampling. The reliability coefficient estimated by Cronbach alpha was found; mastery experience α= .86, vicarious experience α= .75, social persuasions α= .94, physiological state α= .91. Also the reliability coefficient estimated by split-half was found; mastery experience α= .81, vicarious experience α= .73, social persuasions α= .92, physiological state α= .89. Deciding on stability of the scale test-retest applied to 36 studens for 16 days interval. Results showed that mastery experience r= .67, vicarious experience r= .48, social persuasions r= .63, physiological state r= .41. These values indicated that this scale is a reliable instrument for Turkish sampling. In conlusion, Sources of Mathematics Self-Efficacy Scale is a valid and reliable instrument to meeasure sources of mathematics self-efficacy for middle school students in Turkish culture.